Pengaruh Good Corporate Governance terhadap Nilai Perusahaan dimediasi oleh Kinerja Keuangan (Studi pada Perusahaan di Jakarta Islamic Index 70 Periode 2018-2021) - Madania Nurelma Rumaidia; Aulia Fuad Rahman (Ekonomis: Journal of Economics and Business, 2023)
Good corporate governance is considered to be able to create good relations among the company's stakeholders, expected to foster company's long-term goal achievement of maximizing the value of the company. As such, this study aims to examine the effect of good corporate governance—represented by institutional ownership, managerial ownership, and audit committee—on firm value, and to examine the indirect effect through financial performance. The samples include 50 companies incorporated in the Jakarta Islamic Index 70 of the Indonesia Stock Exchange in 2018-2021. The results of the panel data regression analysis exhibit that institutional ownership and managerial ownership have a positive effect on firm value while the audit committee has no effect on firm value. In addition, financial performance cannot mediate the relationship between institutional ownership, managerial ownership, audit committee and firm value.